The complete sequence of mitochondrial genome of Bama miniature pig (Sus scrofa). (2nd January 2016) - Yang, Hu; Xu, Xing-Li; Xu, Dong; Ma, Hai-Ming; Li, Li-li
Abstract: The complete mitochondrial nucleotide sequence of the Bama miniature pig was sequenced in this study. This sequence is homologous to that of the other vertebrate mitochondrial genome. The mitochondrial genome of the Bama miniature pig is 16, 711 bp and contains 37 genes including 22 tRNA genes, 13 protein-coding genes (PCGs), 2 ribosomal RNA genes and 1 control region (D-loop). The 13 PCGs initiated with ATN as start codon and terminated with TAA, TA or T as stop codon. The DNA sequence in the Bama miniature pig D-loop region contains the repeat motif (-TACACGTGCG-) and 5′nucleotide of the first repeat is at the position 796 bp.